بالودي الفترة2019-2022 soptefأهمية جدول سيولة الخزينة في اتخاذ القرارات التمويلية دراسة حالة مؤسسة - رشيدة بوعروة; أحمد قصير; سالم عازب أحمد (university of eloued جامعة الوادي, 2025)
"تهدف هذه الدراسة إلى تسليط الضوء على أهمية جدول سيولة الخزينة في دعم عملية اتخاذ القرارات التمويلية داخل المؤسسة الاقتصادية متعددة الأشغال بالوادي خلال الفترة الممتدة من 2019 إلى 2022. تم تحليل القوائم المالية للمؤسسة باستخدام أدوات التحليل المالي، بالإضافة إلى تطبيق نموذج الانحدار الخطي البسيط عبر البرنامج الإحصائي SPSS V22 ، بهدف استكشاف العلاقة بين مؤشرات السيولة والاستقلالية المالية. أظهرت النتائج أن جدول سيولة الخزينة يُعد أداة تحليلية فعّالة ضمن القوائم المالية، حيث يوفر معلومات دقيقة حول التدفقات النقدية الداخلة والخارجة، مما يُساهم في تحسين جودة القرارات التمويلية، خاصة فيما يتعلق بتقييم كفاية السيولة وتخطيط الاحتياجات التمويلية من مصادر داخلية وخارجية. كما بيّنت الدراسة وجود علاقة بين الاستقلالية المالية وثلاثة مؤشرات للسيولة، إلا أن معظم هذه العلاقات لم تكن ذات دلالة إحصائية قوية. وأشارت نماذج الانحدار إلى أن مؤشرات السيولة تفسر نسبة ضئيلة فقط من التغير في الاستقلالية المالية، مما يدل على أن هناك عوامل أخرى قد تؤثر في هذا الجانب. "This study aims to highlight the importance of the Cash Flow Statement in supporting financial decision-making within the multi-task enterprise located in El Oued, over the period from 2019 to 2022. The financial statements of the enterprise were analyzed using financial analysis tools, in addition to applying a simple linear regression model via the SPSS V22 statistical software, to explore the relationship between liquidity indicators and financial autonomy. The results revealed that the Cash Flow Statement serves as an effective analytical tool within the core financial statements, as it provides accurate information on the enterprise’s cash inflows and outflows. This contributes to enhancing the quality of financial decisions, particularly regarding the assessment of liquidity adequacy and the planning of funding needs from both internal and external sources. The study also demonstrated a relationship between financial autonomy and three liquidity indicators. However, most of these relationships were not statistically significant. Moreover, regression models indicated that liquidity indicators explain only a small portion of the variation in financial autonomy, suggesting the influence of additional underlying factors.
Keywords: جدول سيولة خزينة; قرارات تمويلية; استقلالية مالية; تدفقات نقدية؛; انحدار خطي بسيط; Cash Flow Statement; Financial Decisions; Financial Autonomy; Cash Flows; Simple Linear Regression.